2023
DOI: 10.3393/ac.2021.01011.0144
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into tumor regression grade as a parameter for locally advanced rectal cancer and 5-year overall survival rate

Abstract: Purpose: The standard treatment for locally advanced rectal cancer (LARC) is neoadjuvant chemoradiation (nCRT) followed by surgery. Several parameters are associated with patient survival in LARC. One of these parameters is tumor regression grade (TRG); however, the significance of TRG remains controversial. In this study, we aimed to examine the correlations of TRG with 5-year overall (OS) and relapse-free survival (RFS) and identify other factors that influence the survival rates in LARC after nCRT followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…[ 47 ] Finally, Laohawiriyakamol et al found that the intraoperative perforation was associated with inferior 5-year relapse-free survival. [ 49 ] Combined with our findings, these results highlight the importance of adverse events in rectal cancer surgery. There is an urge for further study for optimal definitions of surgical adverse effects, as well as its impact on the recurrence and survival of LARC patients during the ongoing TME era.…”
Section: Discussionsupporting
confidence: 85%
“…[ 47 ] Finally, Laohawiriyakamol et al found that the intraoperative perforation was associated with inferior 5-year relapse-free survival. [ 49 ] Combined with our findings, these results highlight the importance of adverse events in rectal cancer surgery. There is an urge for further study for optimal definitions of surgical adverse effects, as well as its impact on the recurrence and survival of LARC patients during the ongoing TME era.…”
Section: Discussionsupporting
confidence: 85%
“…In patients with advanced rectal cancer, if there is a good response to treatment after preoperative chemoradiotherapy (CRT), local excision or a nonoperative management, also known as the “watch-and-wait” strategy, may be attempted [ 10 , 11 ]. It is important to select the appropriate candidate for tailored treatment in rectal cancer, which requires accurate diagnosis and assessment of response to preoperative treatment [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%